In vivo measurements of spinal stiffness according to a stepwise increase of axial load - Glaus, Lea Suzanne (Eur J Appl Physiol, 2021)
BACKGROUND: The spine has a complex motor control. Its different stabilization mechanisms through passive, active, and neurological subsystems may result in spinal stiffness. To better understand lumbar spinal motor control, this study aimed to measure the effects of increasing the axial load on spinal stiffness. METHODS: A total of 19 healthy young participants (mean age, 24 ± 2.1 years; 8 males and 11 females) were assessed in an upright standing position. Under different axial loads, the posterior-to-anterior spinal stiffness of the thoracic and lumbar spine was measured. Loads were 0%, 10%, 45%, and 80% of the participant’s body weight. RESULTS: Data were normally distributed and showed excellent reliability. A repeated-measures analysis of variance with a Greenhouse–Geisser correction showed an effect of the loading condition on the mean spinal stiffness [F (2.6, 744) = 3.456, p < 0.001]. Vertebrae and loading had no interaction [F (2.6, 741) = 0.656, p = 0.559]. Post hoc tests using Bonferroni correction revealed no changes with 10% loading (p = 1.000), and with every additional step of loading, spinal stiffness decreased: 0% or 10–45% loading (p < 0.001), 0% or 10–80% loading (p < 0.001), and 45–80% (p < 0.001). CONCLUSION: We conclude that a load of ≥ 45% of the participant’s body weight can lead to changes in the spinal motor control. An axial load of 10% showed no significant changes. Rehabilitation should include high-axial-load exercise if needed in everyday living.